Qualitative and Quantitative Estimation of Water Insoluble Drugs from its Formulations Simultaneously: a Hydrotropic Approach - Sharma, Rajesh; Pathodiya, Geetam; Mishra, Ganesh Prasad (Stamford Journal of Pharmaceutical Sciences, 2011)
Key words: Derivative spectrophotometry method; area under curve method; multi-component method; ciprofloxacin hydrochloride; tinidazole; hydrotropic agent DOI: http://dx.doi.org/10.3329/sjps.v3i2.6541 S.J. Pharm. Sci 3(2): 37-42